Peran Student Well-Being dan School Climate terhadap Prestasi Akademik pada Siswa SMP Yayasan “X” Bandung - Maria Yuni Megarini Cahyono; Trisa Genia Chrisantiana; Ellen Theresia (Humanitas (Jurnal Psikologi), 2021)
This study aims to determine the role of student well-being and school climate on the academic achievements of "X" foundation junior high school students from grades 7, 8, and 9 in Bandung. This study involved 793 students. The measuring instrument used consisted of two questionnaires, namely Student well-being questionnaire and school climate questionnaire. Academic achievement are obtained through the average midterm grade 2019/2020. Data processing with Multiple Regression test. The results showed that student well-being and school climate had a significant role (F = 7.971, sig =0.000) both together and separately for achievement. Students with many successful experiences, close relationships, feeling accepted, and having endurance will be able to produce high academic achievement. School is a vehicle that is expected to create a conducive learning environment for students. Keywords: Student well-being, school climate, academic achievement, junior high school students